Influencia de las raciones alimenticias en el crecimiento de neonatos de Caiman crocodilus (Linnaeus 1758) en cautiverio con fines de conservación. Iquitos, Perú. 2020 - Espinar Cora, Leonardo Camilo (2024)
The study was carried out in the Temporary Custody Center and Zoo “Fundo Pedrito”, in the Barrio Florido town center, district of Punchana, it is an experimental quantitative research, the Completely Random Design (DCA) was used with nine units. experimental experiments distributed randomly to determine the influence of food rations on the biological development of Caiman crocodrilus neonates) for four months. T1 was the one that obtained the greatest increases from 7.0 g to 11.20 g, followed by treatment T0 between 4.30 g and 6.50 g. and the one that obtained the smallest increases are those in treatment T2 with 3.0 g to 4.0 g. Regarding the total length of the neonates, treatment T1 reached an average total length of 17.47 cm, followed by T2 with an average of 15.89 cm and finally T0 with 14.9 cm. In the analysis of variance, the total length indicates a significantly high statistical difference between the treatments, the treatment that most influences the growth of the neonates is T1 (fed with fish) with an average of 17.47 cm, statistically surpassing the others. treatments, the relationship coefficient shows a low intermediate level of association of 44.25% between total length and food consumption. Regarding the average weights, in T1 they reached a highest average weight of 46.44 g, followed by T2 with a weight of 45.67 g, while T0 with 34.78 g obtained the lowest weight. The analysis of variance of the weight averages shows that There is no statistical significance, since Fc= 0.15279133 is less than Ft=5.14325285. While the analysis of variance of food consumption shows a high significant statistical difference between treatments, since Fc=49.20941098** is greater than Ft=18.51282051, so the Duncan test indicates that the averages of treatments T1 and T2 are absolutely discrepant among themselves, where T1 occupies the first place with an average of 599.66667 g, statistically surpassing T2 who occupied the subsequent position with an average of 260.3333333 g, the control did not prosper, these variables show a moderately high level of correlation of 79.08% of association between total weight on food consumption in neonates.